2023
DOI: 10.1186/s13048-023-01180-8
|View full text |Cite
|
Sign up to set email alerts
|

SPON1 is an independent prognostic biomarker for ovarian cancer

Abstract: Background Ovarian cancer has the worst outcome among gynecological malignancies; therefore, biomarkers that could contribute to the early diagnosis and/or prognosis prediction are urgently required. In the present study, we focused on the secreted protein spondin-1 (SPON1) and clarified the prognostic relevance in ovarian cancer. Methods We developed a monoclonal antibody (mAb) that selectively recognizes SPON1. Using this specific mAb, we determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…shown to be involved in the response of the silkworm after fluoride infestation (Yuxia et al, 2020). In this predicted to involved in the immunological functions of larvae (Zhang, Xue, et al, 2013), another group revealed the expression of Hemagglutinin Neuraminidase (HN, BMSK0000689) upregulates the SAPK/JNK pathway leading to transactivation of c-Jun which in turn activates apoptosis signaling (Rajmani et al, 2015), other genes such as Phosphoribosyl Pyrophosphate Synthetases 2 (PRPS2, BMSK0012236), Cytosolic 10-Formyltetrahydrofolate Dehydrogenase (ALDH1L, BMSK0009300), Spondin 1 (SPON1, BMSK0007887), and Cathepsin B (CTSB, BMSK0010120) have been reported to associate with early diagnosis (Liu et al, 2022), development (Krupenko & Krupenko, 2018) and prognosis of cancer (Ma et al, 2022;Miyakawa et al, 2023)…”
Section: Regulatory Network Of Delncrna-demrnamentioning
confidence: 99%
“…shown to be involved in the response of the silkworm after fluoride infestation (Yuxia et al, 2020). In this predicted to involved in the immunological functions of larvae (Zhang, Xue, et al, 2013), another group revealed the expression of Hemagglutinin Neuraminidase (HN, BMSK0000689) upregulates the SAPK/JNK pathway leading to transactivation of c-Jun which in turn activates apoptosis signaling (Rajmani et al, 2015), other genes such as Phosphoribosyl Pyrophosphate Synthetases 2 (PRPS2, BMSK0012236), Cytosolic 10-Formyltetrahydrofolate Dehydrogenase (ALDH1L, BMSK0009300), Spondin 1 (SPON1, BMSK0007887), and Cathepsin B (CTSB, BMSK0010120) have been reported to associate with early diagnosis (Liu et al, 2022), development (Krupenko & Krupenko, 2018) and prognosis of cancer (Ma et al, 2022;Miyakawa et al, 2023)…”
Section: Regulatory Network Of Delncrna-demrnamentioning
confidence: 99%